Institutional Capacity of BPKAD in Increasing Local Own-Source Revenue in Southwest Papua Province A Diagnosis of Administrative Equilibrium in a Newly Formed Autonomous Region - Ernawati Miyane Naa; Muh. Yunus; Muh. Akmal Ibrahim (Journal of Communication and Social Sciences, 2026)
The formation of new autonomous regions demands strengthening the institutional capacity of regional finance managers so they can increase local own-source revenue (PAD), yet that capacity is often read merely as a resource-shortage problem. This study analyzes the institutional capacity of the Regional Financial and Asset Management Agency (BPKAD) of Southwest Papua Province through Grindle and Hilderbrand’s capacity-development dimensions—institutional context, human-resource development, organizational strengthening, enabling environment, and change dynamics. A qualitative case-study design was used; data were collected through interviews, documentation, and observation, then analyzed thematically. The findings show that institutional capacity sits in an administrative equilibrium—a stable balance at a low level in which structure, competence, and regulation lock one another onto revenue sources that run automatically. Officials are skilled at serving but are not prepared to pursue new sources; the structure is complete yet lacks owners for its functions; and operational regulation for sources that require initiative is absent, so levies are recorded at zero even though the legal umbrella is complete. The capacity foundation is not empty but filled and yet severed from its functions; strengthening it requires filling the operational-regulation layer as a lever that triggers chained adjustments in structure, competence, and incentives.